Acidic oral moisturizers with pH below 6.7 may be harmful to teeth depending on formulation: a short report - Delgado AJ; Olafsson VG (Dove Medical Press, 2017)
Alex J Delgado,1 Vilhelm G Olafsson2,3 1Department of Restorative Dental Sciences, University of Florida, Gainesville, FL, USA; 2Department of Operative Dentistry, Faculty of Odontology, University of Iceland and Private Practice, Reykjavic, Iceland; 3Department of Operative Dentistry, School of Dentistry at the University of North Carolina, Chapel Hill, NC, USA Abstract: Xerostomia affects 30% of the population and manifests as a side effect of medications, systemic diseases, or cancer therapy. Oral moisturizers are prescribed to overcome the ailments of dry mouth and its symptoms. It is imperative that these products help to restore hyposalivation and that they do not present any secondary effect that can harm oral health. It has been shown in the literature that some oral moisturizers may have an erosive potential due to their acidic pH, which is below the critical pH of dentin and enamel. The purpose of this paper was to make clinicians aware of the erosive potential of these products and make recommendations to manufactures for future formulations avoiding acidic pH. For this reason, care should be taken to formulate these products with safe pH values for both enamel and root dentin which, based on specific formulation should be around 6.7 or higher. Keywords: oral moisturizers, pH, erosion, caries, xerostomia, dry mouth